Relative Abundance, Activity Patterns And Habitat Use Of The Asian Elephants In The Belum-temengor Forest Complex, Perak - Sagtia Siwan, Elangkumaran (2019)
xvi RELATIVE ABUNDANCE, ACTIVITY PATTERNS AND HABITAT USE OF THE ASIAN ELEPHANTS IN THE BELUM-TEMENGOR FOREST COMPLEX, PERAK ABSTRACT The ecology of Asian elephants (Elephas maximus) in the tropical forests of Peninsular Malaysia inadequately studied, even though it is an iconic flagship species for the region. Classified as endangered under the IUCN Red List of Threatened Species, a total of 1,223-1,677 wild Asian elephants estimated in Peninsular Malaysia, which are facing various threats from habitat fragmentation, degradation and conversion as well as human elephant conflict, roadkill and poaching. Camera trapping (21, 263 trap nights) and sign survey (2665 km distant) were used to assess relative abundance, activity patterns and habitat use of Asian elephants within priority area for elephant conservation in Peninsular Malaysia; Belum-Temengor Forest Complex. The overall relative abundance index found to be 2.13±0.48. The activity patterns of the Asian elephants was found to be cathemeral and significantly different (W=44.50, p=0.040) only during the daytime between two sites within the forest complex; Royal Belum State Park (a primary forest) and Temengor Forest Reserve (a secondary forest). The habitat use of Asian elephants broadly indicates the importance of the combined effect of rivers and patches of forest that are less dense in vegetative cover.